2020
DOI: 10.3390/min11010002
|View full text |Cite
|
Sign up to set email alerts
|

Tennantite–Tetrahedrite-Series Minerals and Related Pyrite in the Nibao Carlin-Type Gold Deposit, Guizhou, SW China

Abstract: A number of sediment-hosted, Carlin-type/-like gold deposits are distributed in the Youjiang basin of SW China. The gold ores are characterized by high As, Hg, and Sb contents but with low base metal contents (Cu+Pb+Zn < 500–1000 ppm). The Nibao deposit is unique among these gold deposits by having tennantite–tetrahedrite-series minerals in its ores. The deposit is also unique in being primarily hosted in the relatively unreactive siliceous pyroclastic rocks, unlike classic Carlin-type gold deposits that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…Following the approval of tennantite-(Hg) from the Lengenbach quarry, two other occurrences have been reported. Wei et al (2021) described tennantite-(Hg) (Hg up to 1.34 apfu), as μm-sized (~ 1-2 μm) grains associated with tennantite-(Zn), from the Nibao Carlintype Au deposit, Guizhou (China), whereas Ansermet et al (2021) (N. Meisser, pers. comm.…”
Section: Other Findings Of Tennantite-(hg)mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the approval of tennantite-(Hg) from the Lengenbach quarry, two other occurrences have been reported. Wei et al (2021) described tennantite-(Hg) (Hg up to 1.34 apfu), as μm-sized (~ 1-2 μm) grains associated with tennantite-(Zn), from the Nibao Carlintype Au deposit, Guizhou (China), whereas Ansermet et al (2021) (N. Meisser, pers. comm.…”
Section: Other Findings Of Tennantite-(hg)mentioning
confidence: 99%
“…Following the approval of tennantite-(Hg) from the Lengenbach quarry, two other occurrences have been reported. Wei et al (2021) described tennantite-(Hg) (Hg up to 1.34 apfu), as μm-sized (∼1-2 μm) grains associated with tennantite-(Zn), from the Nibao Carlin-type Au deposit, Guizhou, China, whereas Ansermet et al (2021) reported tennantite-(Hg) from the Chandolin Alp, Valais, Switzerland, as a 70 μm anhedral grain associated with gold, bismuth, covellite, hessite, spionkopite and chalcocite, all included in bornite. On the basis of energy-dispersive spectroscopy analyses, the chemical formula, recalculated assuming ΣMe = 16 apfu, is Cu 9.62 Hg 2.02 (As 4.05 Sb 0.31 ) Σ4.36 S 13.37 (N. Meisser, pers.…”
Section: Other Findings Of Tennantite-(hg)mentioning
confidence: 99%
“…Recently, Wei et al, (2021) reported that tennantite could act as one of major Au-bearing ore minerals, suggesting that its coexistence with Au-bearing pyrite might indicate derivation from oxidized hydrothermal fluids. The presence of tennantite was suggested to be an indicator of magmatic-hydrothermal origin of ore-forming fluids (Staude et al, 2010).…”
Section: Implications Of Intrusive Complex For Ore-forming Processesmentioning
confidence: 99%
“…The Youjiang basin hosts clusters of Carlin-type Au, Sb, and Hg-Tl deposits (Figure 1) [1][2][3][4][5][6][7][8], such that it is the second largest low-temperature Carlin-type Au mineralized area in the world, after Nevada, USA [9][10][11][12][13]. The Au and Sb deposits in the Youjiang Basin are primarily located within Southwestern Guizhou and account for more than 70% of the deposits and endowments.…”
Section: Introductionmentioning
confidence: 99%